Twist Solid GMS560 v0.6.1 references fuseq_wes - Almlöf, Jonas (Uppsala University, 2023)
The data included here are part of a collection of different types of reference data used in the bioinformatic analysis pipeline called Twist Solid GMS560. The pipeline is based on the Hydra-genetics framework and analyses NGS short read data from the GMS560 Twist panel which is used on solid cancer samples.

The data in this specific item include general publicly available reference files used in the pipeline by the fusion calling program FuSeq_WES (https://github.com/nghiavtr/FuSeq_WES). Downloading data from here will ensure compatible and correct versions.
Keywords: Other health sciences not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Other Health Sciences; Annan hälsovetenskap